Knowledge and Attitude of Students on Antimicrobial Resistance at Debre Markos University, Ethiopia - Desalegne Amare Zelellw; Habtamu Mellie Bizuayehu (International Journal of Public Health Science (IJPHS), 2016)
Irrational use of medicines is a key reason for the increase and spread of antimicrobial resistance and it is a global concern. It is a fast mounting universal crisis. The main of this study of this study was to assess knowledge, attitude and practice of university students on antimicrobial resistance at Debre Markos University. Institutional based comparative cross-sectional survey was conducted from June to July with total sample size of 670. Participants were selected using simple random sampling method using random number table. Data clerk double entered the data into Epi data version 3.1 and transferred to SPSS Windows software version 21.0. Those variables that had associations at binary stage with p-value < 0.1, not collinear and biologically important variables were entered in to multiple logistic regression models. The cut off point for association was p-value < 0.05. About 14.8% study participants had adequate knowledge towards drug resistance.  Rural residences of the participants were significantly associated with drug resistance as compared to urban residence. Knowledgeable participants were significantly protective to self- medication and drug resistance as compare to those who had inadequate knowledge and participants who had positive attitude were positively associated with self-medication as compare to those who had negative attitude. The overall knowledge of participants regarding to antimicrobial resistance was low. In the other hand, majority of participants had positive attitude. Those participants who had positive attitude were significantly associated with antimicrobial resistance as compared to who had negative attitude.